1986
DOI: 10.1007/bf00211536
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological aspects of idiopathic peripheral facial palsy

Abstract: Four hundred and twenty seven idiopathic peripheral facial palsy (IPFP) patients admitted to the Otolaryngology Department of the Soroka Medical Center in southern Israel between 1978 and 1982 were characterized and analyzed by age, sex and season of illness. An average annual incidence rate of 33.6 patients per 100,000 inhabitans was calculated which is considered to be the highest incidence reported so far, and may be explained by the very high coverage of the "Sick Fund" insurance in the region and by the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
2

Year Published

1989
1989
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 17 publications
5
28
2
Order By: Relevance
“…Literature reports on the seasonal distribution of Bell's palsy are varied and contradictory [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Our study did not reveal any seasonal distribution of the disease, neither in the total group of patients nor when dividing them by sex.…”
Section: Discussioncontrasting
confidence: 34%
See 4 more Smart Citations
“…Literature reports on the seasonal distribution of Bell's palsy are varied and contradictory [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Our study did not reveal any seasonal distribution of the disease, neither in the total group of patients nor when dividing them by sex.…”
Section: Discussioncontrasting
confidence: 34%
“…Leibowitz [18] claimed that younger ages were more affected in the cold period of the year, while older patients were more affected in the warm period. Tovi et al [21] reported a higher frequency of the disease in winter for ages less than 30 years, while there is no seasonal distribution in patients older than 30 years. Adour and Winged [8], dividing the patients into two age-groups, over and under 35 years of age, did not observe any seasonal distribution, neither in each sex group nor in the total of the patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations